Pembuatan Baterai Kering Menggunakan Karbon Aktif dari Cangkang Kelapa Sawit dan Asam Nitrat (HNO3) sebagai Aktivator - Berlian Tiara; Tri Larasati; Ida Febriana; Iriani Reka Septiana; Nurul Kholidah (Talenta Publisher (Universitas Sumatera Utara), 2026)
Activated carbon from palm kernel shells has the potential to be an environmentally friendly material to replace heavy metals in dry batteries. The objective of this study is to analyze the effect of variations in HNO₃ concentration (0.5 M; 1 M; 1.5 M; 2 M; and 2.5 M) and to evaluate its performance as a dry battery electrode material using 1 M NaOH and 1 M H₃PO₄ electrolytes. The process involved carbonisation and chemical activation using HNO₃, followed by proximate analysis, iodine number testing, and surface morphology analysis using a Scanning Electron Microscope (SEM). The results showed the best performance was achieved at an HNO₃ concentration of 1 M with a voltage of 3.66 V, current of 5.55 mA, and power of 20.31 mW when using NaOH electrolyte. Conversely, at an HNO₃ concentration of 2.5 M with H₃PO₄ electrolyte, the lowest performance was achieved at a voltage of 1.94 V, current of 0.79 mA, and power of 1.53 mW due to pore damage. This study demonstrates the potential of oil palm shells as a raw material for environmentally friendly and sustainable batteries.